Facilitators and Barriers to Providing Breastfeeding and Lactation Support to Families in Appalachia: A Mixed-Methods Study With Lactation Professionals and Supporters. (7th June 2021) - Seiger, Emily; Wasser, Heather; Foster, Grace; Sideek, Ruwaydah; Hutchinson, Stephanie; Martin, Stephanie
Abstract: Objectives: Breastfeeding rates in Appalachia are lower than the rest of the United States and contribute to poor health outcomes in the region. Lactation professionals and supporters are critical to improving low breastfeeding rates, but there is a lack of research on their experiences providing support to families, particularly in Appalachia. This implementation research explored the facilitators and barriers that lactation professionals and supporters in Appalachia experience when supporting breastfeeding. Methods: This mixed-methods study included a survey with members of the Appalachian Breastfeeding Network and in-depth interviews with a sub-sample of survey participants. Survey data were descriptively analyzed in Stata and interview transcripts were analyzed thematically using an inductive approach in ATLAS.ti. Data from both phases were analyzed according to certification type and participants who worked in WIC vs. non-WIC settings. Results: The survey was completed by 89 lactation professionals and supporters from 14 states; 33% were International Board Certified Lactation Consultants (IBCLCs) and 47% had other lactation certifications; 24% worked at WIC. Twenty participants from 7 states participated in in-depth interviews. Barriers identified in both phases included being the only lactation professional or supporter in several counties, cross-cultural communication, racism, feeling like their expertise is undervalued and counseling clients around drug use, with negative views of breastfeeding, or who lack family support. The qualitative phase revealed counseling around mental health/trauma, chest feeding, and re-lactation as issues they need more information about. Facilitators included the support from other lactation professionals and supporters, being able to refer clients to the Appalachian Breastfeeding Network help line, and including other family members in lactation counseling. Social media and telehealth were discussed as both barriers and facilitators. Conclusions: More lactation professionals and supporters that reflect the population served are needed in rural areas. Additional training for providing support around mental health, chest feeding, drug use, etc. is essential. Lactation professionals and supporters must be included in future efforts to solve these challenges. Funding Sources: N/A.